Eurobarometer 43.0: Cross-border purchases, smoking habits, and cancer risks, March-April 1995 - Reif, Karlheinz; Marlier, Eric; Commission of the European Communities (Commission of the European Communities, 1997)
This round of Eurobarometer surveys queried respondents on standard Eurobarometer measures such as public awareness of and attitudes toward the European Union (EU), and also focused on cross-border purchases, tobacco smoking habits, and risks of cancer. Respondents were queried about what consumer products they purchased from other member countries, their satisfaction with products purchased from member countries, and any complaints made in connection with cross-border purchases. The respondents were also asked about their attitudes and behavior toward smoking. Questions focused on the type of tobacco products used, the number of cigarettes consumed daily, the desire of smokers to limit their consumption, the attitudes of both smokers and nonsmokers toward the use of tobacco products in public, opinions regarding regulations prohibiting smoking in some public places, feelings about smoke in the workplace, and the advertising of tobacco products. A number of questions dealt with major diseases, the prevention of cancer, conditions causing increased risks of cancer, and knowledge of the ´European Code of Cancer´ (a set of elementary rules, developed by a committee of cancer experts, for the possible prevention of cancer). Demographic and other background information was gathered on the number of people residing in the home, size of locality, household income, and region of residence, as well as the respondent´s age, sex, marital status, age when completed education, occupation, previous occupation, and left-right political self-placement.

Denna omgång av Eurobarometern undersökte respondenternas inställning till typiska Eurobarometer-mått såsom allmänhetens medvetenhet om, och attityder till, Europeiska Unionen (EU). Därtill sattes fokus på gränsöverskridande konsumtion, tobaksvanor och cancerrisk. Respondenterna tillfrågades om deras inköp av konsumentprodukter från andra medlemsländer, deras tillfredsställelse med dessa samt eventuella klagomål i samband med inköpen. Frågor ställdes också både gällande attityder mot rökning och faktiska rökvanor. Mer specifikt ställdes frågor om vilka typer av tobaksprodukter som används, antalet cigaretter som konsumeras dagligen, rökares önskan om att begränsa sin konsumtion, rökares såväl som icke-rökares attityder till användningen av tobaksprodukter på offentliga platser, åsikter om rökförbud på vissa offentliga platser, inställning till rökning på arbetsplatsen och till tobaksreklam. Ett antal frågor rörde allvarliga sjukdomar, förebyggande av cancer, omständigheter som ökar risken för cancer samt kunskap om den europeiska cancerplanen ’European Code of Cancer’ (en uppsättning av grundläggande föreskrifter, utvecklade av en kommitté av cancerexperter, i syfte att förebygga cancer). Demografisk information samlades in gällande antalet personer i hushållet, ortsstorlek, hushållsinkomst och tillhörande region. Annan bakgrundsinformation som samlades in var respondentens ålder, kön, civilstånd, ålder vid avslutad utbildning, nuvarande och tidigare yrken och självplacering på den politiska vänster-högerskalan.
Eurobarometer 43.0: Cross-border purchases, smoking habits, and cancer risks, March-April 1995
EB43.0
Keywords: cancer; cancer; Smoking; Rökning; Tobacco Products; Tobaksprodukter; Tobacco Use; Tobaksanvändning; General health and well-being; Allmän hälsa och välbefinnande; International politics and organisations; Internationell politik och organisationer; TRADE, INDUSTRY AND MARKETS; HANDEL, INDUSTRI OCH MARKNADER; Social Sciences; Samhällsvetenskap; Diet and nutrition; Kost och näring